Multiplex frequency modulation and its application to stereo broadcasting : Research reports and publications on multiplex frequency modulation, subterranean propagation of electromagnetic waves, analog computer, class C amplifiers and spark discharge. - Olen, Carl Ludwig (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Ing.) -- University of Stellenbosch, 1965.